2009
DOI: 10.1074/jbc.m808337200
|View full text |Cite
|
Sign up to set email alerts
|

Wnt11 Promotes Osteoblast Maturation and Mineralization through R-spondin 2

Abstract: Wnt11 signals through both canonical (␤-catenin) and noncanonical pathways and is up-regulated during osteoblast differentiation and fracture healing. In these studies, we evaluated the role of Wnt11 during osteoblastogenesis. Wnt11 overexpression in MC3T3E1 pre-osteoblasts increases ␤-catenin accumulation and promotes bone morphogenetic protein (BMP)-induced expression of alkaline phosphatase and mineralization. Wnt11 dramatically increases expression of the osteoblast-associated genes Dmp1 (dentin matrix pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 39 publications
4
97
3
Order By: Relevance
“…Whereas the presence of Wnt ligands in the BM niche is well established, expression of R-spondins in the BM microenvironment thus far has remained largely unexplored. Because autocrine R-spondins have been suggested to regulate differentiation of osteoblasts (38), which are important constituents of the MM niche (39,40), we hypothesized that osteoblasts could be a major source of R-spondins driving oncogenic Wnt signaling. Corroborating this hypothesis, we found expression of several R-spondins in (pre)osteoblasts and demonstrated that (pre)osteoblast-conditioned media robustly synergized with Wnt ligands in activating Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the presence of Wnt ligands in the BM niche is well established, expression of R-spondins in the BM microenvironment thus far has remained largely unexplored. Because autocrine R-spondins have been suggested to regulate differentiation of osteoblasts (38), which are important constituents of the MM niche (39,40), we hypothesized that osteoblasts could be a major source of R-spondins driving oncogenic Wnt signaling. Corroborating this hypothesis, we found expression of several R-spondins in (pre)osteoblasts and demonstrated that (pre)osteoblast-conditioned media robustly synergized with Wnt ligands in activating Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the source of R-spondins remains to be defined. Prime candidates are osteoblasts, which have recently been suggested to use autocrine R-spondin for their differentiation (38) and, moreover, are key constituents of the MM niche (39,40). We therefore analyzed R-spondin mRNA expression in primary human osteoblasts (hOB) by qPCR.…”
Section: R-spondins Potentiate Wnt Signaling In MM In a Lgr4-dependentmentioning
confidence: 99%
“…Activation of Wnt11 through β‐catenin–independent Wnt signaling is essential for embryonic cardiac development 142. In terms of its role in osteogenic development, Wnt11 activation in MC3T3E1 preosteoblasts increases β‐catenin accumulation, promoting BMP‐induced osteoblast maturation and mineralization through canonical Wnt signaling 143. Wnt11 induces the expression of R‐spondin 2, a secreted enhancer of Wnt signaling, which stimulates osteoblastogenesis through increasing the expression of osteogenic factors, such as Dmp1 (dentin matrix protein 1), Phex (phosphate‐regulating endopeptidase homolog), and Bsp (bone sialoprotein) 143…”
Section: Implication Of Noncanonical Wnt Signaling In Vcmentioning
confidence: 99%
“…The behavior of Sostdc1-positive cells is similar to osteochondroprogenitor cells in the periosteum that, using lineage tracing, make a major contribution to the soft callus [194]. The role of Sostdc1 as a WNT antagonist, and the known role of WNT/β-catenin signaling to promote osteogenic [198] and chondrogenic [199,200] differentiation and maturation, suggests that Sostdc1 may act as the rate-limiting inhibitor of the differentiation of pluripotent periosteal cells during fracture repair. Indeed, we observe a temporal shift in the frequency of MSC and OB subpopulations during fracture repair in Sostdc1 -/-mice, as well as greater area-under-curve of OBs, but not of MSCs, indicating more rapid activation of migration, proliferation and differentiation of MSCs and OBs, and further supporting the role of Sostdc1 as an osteochondral progenitor gatekeeper.…”
Section: Discussionmentioning
confidence: 82%